Simulation of vapor-liquid equilibrium in system: a,g-dichlorohydrin–Α-monochlorohydrin–glycerol–hydrogen chloride–water - S. M. Zanaveskina; Yu. A. Pisarenko; G. S. Dmitriev; L. N. Zanaveskin (Тонкие химические технологии, 2013)
. Both the experimental LLE and VLE data were compared with the correlated values obtained by means of the NRTL equation. Satisfactory agreement between the calculated values and experimental data was achieved